Aqueous dispersion for forming electromagnetic wave shielding film
By using an aqueous dispersion on the resin substrate, combining the carbamate dispersion and carbon black, the problem of insufficient coating and adhesion of the electromagnetic wave shielding film in the prior art is solved, and an efficient electromagnetic wave shielding effect is achieved.
Patent Information
- Application Number
- CN202380038206.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-28
- Filing Date
- 2023-10-17
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to obtain an electromagnetic wave shielding film with excellent electrical properties while maintaining good coating properties and adhesion, especially in applications on resin substrates.
Using an aqueous dispersion, containing water, carbon black and urethane dispersion, the mass ratio of the particle mass of the urethane dispersion to carbon black is between 0.55 and 1.30, and the average particle size is less than 50 nm, and can The volatile alkali and gelling agent are selected, and the particle size and surface area are measured by laser diffraction method and nitrogen adsorption method. Combined with the alkali-swelling association gelling agent, an electromagnetic wave shielding film is formed.
The electromagnetic wave shielding film coated on the resin substrate has good coating properties and adhesion, while obtaining low surface resistivity and high electromagnetic wave absorption, which is suitable for electromagnetic wave shielding applications.
Smart Images

Figure BDA0005116528050000121 
Figure BDA0005116528050000131 
Figure BDA0005116528050000141
Abstract
Description
Technical Field
[0001] The present invention relates to an aqueous dispersion for forming an electromagnetic wave shielding film. Background Art
[0002] In recent years, electronic devices such as personal computers, mobile phones, and tablet terminals have become popular, and they can be used to exchange information anywhere, indoors and outdoors, not only in homes and companies. However, while these electronic devices are highly convenient, the unwanted electromagnetic waves (noise) generated by the electronic devices have adverse effects such as malfunctions on other electronic devices or electronic products, which has become a problem. In order to solve such problems, various electromagnetic wave suppression sheets have been disclosed.
[0003] Patent document 1 discloses a composition for forming an electromagnetic wave shielding film, which is characterized in that it is used to form a film with an electromagnetic wave shielding effect on a component that generates electromagnetic waves and / or a component that covers the component, and the composition for forming an electromagnetic wave shielding film is in a liquid state, sprayed by inkjet, and contains a powder composed of an electromagnetic wave suppressing material.
[0004] Patent document 2 discloses an electromagnetic wave suppression sheet, characterized in that it is composed of a resin composition (A) containing an electromagnetic wave suppression substance, and the resin composition (A) is a resin composition containing a polyurethane resin (a1) having a 100% modulus of 1 to 7 MPa.
[0005] Patent Document 3 discloses a radio wave absorbing coating composition comprising a coating film-forming resin and pitch-based carbon fibers, wherein the content of the pitch-based carbon fibers is 2 to 15 volume % relative to 100 volume % of the solid content of the composition.
[0006] Patent Document 4 discloses an electromagnetic wave shielding coating material characterized by containing a resin obtained by mixing a water-dispersible copolymer resin compound and a solvent-soluble copolymer resin compound, a nonionic surfactant, and a conductive material.
[0007] Patent Document 5 discloses an electromagnetic wave absorbing coating agent containing water, an aqueous emulsion or a thickener, and a magnetic body-supporting coiled carbon fiber.
[0008] Patent document 6 discloses an inkjet recording ink, which is formed by dispersing composite particles containing a black pigment and a resin, wherein the black pigment includes carbon particles having a hollow structure, and the resin is an acrylic resin having an acid value of 10 mgKOH / g or more and 150 mgKOH / g or less and a neutralization rate of less than 80%.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2013-168399
[0012] Patent Document 2: Japanese Patent Application Publication No. 2017-45782
[0013] Patent Document 3: Japanese Patent Application Publication No. 2020-111730
[0014] Patent Document 4: Japanese Patent Application Publication No. 2015-220233
[0015] Patent Document 5: Japanese Patent Application Publication No. 2015-172152
[0016] Patent Document 6: Japanese Patent No. 5930176 Summary of the invention
[0017] Problem that the invention aims to solve
[0018] The present invention provides a novel aqueous dispersion for forming an electromagnetic wave shielding film, which has excellent coating properties and adhesion to a resin substrate and can obtain an electromagnetic wave shielding film having excellent electrical properties.
[0019] Solutions for solving problems
[0020] The present inventors have conducted intensive research and have found that the above-mentioned technical problems can be solved by the following means, thereby completing the present invention. That is, the present invention is as follows.
[0021] <Aspect 1> An aqueous dispersion for forming an electromagnetic wave shielding film, comprising water, carbon black, and a urethane dispersion,
[0022] The ratio of the mass of the particles of the urethane dispersion to the mass of the carbon black is 0.55 to 1.30.
[0023] <Aspect 2> The aqueous dispersion according to aspect 1, wherein a ratio of the mass of the particles of the urethane dispersion to the mass of the carbon black is 0.85 to 1.15.
[0024] <Aspect 3> The aqueous dispersion according to aspect 1 or 2, wherein the particles of the urethane dispersion have an average particle size of 50 nm or less as measured by a laser diffraction method.
[0025] <Aspect 4> The aqueous dispersion according to any one of aspects 1 to 3, further comprising a volatile base, wherein the content of the volatile base is 0.1 to 3.0% by mass.
[0026] <Aspect 5> The aqueous dispersion according to any one of aspects 1 to 4, further comprising a gelling agent.
[0027] <Aspect 6> The aqueous dispersion according to aspect 5, wherein the gelling agent is an alkali-swellable associative gelling agent.
[0028] <Aspect 7> The aqueous dispersion according to any one of aspects 1 to 6, wherein the carbon black has a hollow shell structure and a BET specific surface area measured by a nitrogen adsorption method of 1000 m 2 / g or less.
[0029] <Aspect 8> A method for producing an electromagnetic wave absorbing sheet, comprising the steps of applying the aqueous dispersion according to any one of aspects 1 to 7 onto a resin substrate and drying the dispersion to obtain an electromagnetic wave shielding film.
[0030] <Aspect 9> The method according to aspect 8, wherein the surface resistivity of the electromagnetic shielding film measured by a four-probe method is 400Ω / □ or less.
[0031] <Aspect 10> An electromagnetic wave absorbing sheet comprising a resin substrate and an electromagnetic wave shielding film on the resin substrate,
[0032] The electromagnetic wave shielding film is obtained by drying the aqueous dispersion according to any one of aspects 1 to 7.
[0033] <Aspect 11> The electromagnetic wave absorbing sheet according to aspect 10, wherein the electromagnetic wave shielding film has a dry film thickness of 100 μm or less and a volume resistivity of 1.0 Ω·cm or less.
[0034] Effects of the Invention
[0035] The present invention provides a novel aqueous dispersion for forming an electromagnetic wave shielding film, which has excellent coating properties and adhesion to a resin substrate and can produce an electromagnetic wave shielding film having excellent electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a graph showing the relationship between the ratio of the mass of the binder to the mass of carbon black and the surface resistivity of the obtained electromagnetic wave shielding film when a urethane dispersion is used as the binder.
[0037] Figure 2 This is a graph showing the relationship between the ratio of the mass of the binder to the mass of carbon black and the surface resistivity of the obtained electromagnetic wave shielding film when styrene acrylic resin or acrylic resin is used as the binder. DETAILED DESCRIPTION
[0038] 《Aqueous dispersion for forming electromagnetic wave shielding film》
[0039] The aqueous dispersion for forming an electromagnetic wave shielding film of the present invention contains water, carbon black, and a urethane dispersion.
[0040] The ratio of the mass of the particles of the urethane dispersion to the mass of the carbon black is 0.55 to 1.20.
[0041] The present inventors have found that, according to the above-mentioned configuration, coating properties with respect to a resin substrate are good and an electromagnetic wave shielding film having good electrical properties can be obtained.
[0042] The mass ratio of the particles of the carbamate dispersion to the mass ratio of the carbon black can be 0.55 or more, 0.60 or more, 0.65 or more, 0.70 or more, 0.80 or more, or 0.85 or less, and can be 1.30 or less, 1.20 or less, 1.15 or less, 1.10 or less, 1.05 or less, or 1.00 or less. In addition, the surface resistivity of the electromagnetic wave shielding film obtained at a mass ratio within such a range becomes a low value, thereby achieving good electromagnetic wave absorptivity. Although it is not desired to be bound by theory, it can be considered that by such a ratio, the carbon black can be appropriately distributed without covering the surface of the carbon black and hindering the conductivity, so that such good electromagnetic wave absorptivity can be obtained.
[0043] The aqueous dispersion for forming an electromagnetic wave shielding film of the present invention may contain any dispersant. In this case, the mass ratio of the dispersant to carbon black may be 0.17 or more, 0.18 or more, or 0.19 or more, and the mass ratio may be 0.40 or less, 0.35 or less, 0.30 or less, 0.28 or less, 0.25 or less, or 0.23 or less.
[0044] The electromagnetic shielding film-forming aqueous dispersion of the present invention preferably contains a volatile base from the viewpoint of suppressing shrinkage of the coating film.
[0045] The electromagnetic shielding film-forming aqueous dispersion of the present invention preferably further contains a gelling agent from the viewpoint of obtaining an electromagnetic shielding film having a desired thickness, for example, an electromagnetic shielding film having a DRY film thickness of 5 μm or more, 7 μm or more, 10 μm or more, 15 μm or more, 17 μm or more, 20 μm or more, 25 μm or more, or 30 μm or more.
[0046] Hereinafter, each constituent element of the present invention will be described.
[0047] <water>
[0048] As water, distilled water, ion-exchanged water, or the like can be used.
[0049] Carbon Black
[0050] As carbon black, for example, Ketjen black etc. can be used. Carbon black may have a hollow shell-like structure.
[0051] The BET specific surface area of carbon black measured by nitrogen adsorption method can be 1000 m 2 / g or less, 900m 2 / g or less, 800m 2 / g or less, 700m 2 / g or less, 600m 2 / g or less, 500m 2 / g or less, 400m 2 / g or below 300m 2 / g or less. The BET specific surface area may also be 100m 2 / g or above, or 200m 2 / g or above.
[0052] The content of carbon black can be 5 mass %, 6 mass % or 7 mass % or more relative to the mass of the aqueous dispersion for forming the electromagnetic wave shielding film, and can be 15 mass %, 12 mass %, 10 mass % or less or 8 mass % or less.
[0053] 〈Dispersant〉
[0054] As the dispersant, for example, water-soluble resins such as polyvinyl pyrrolidone, polyvinyl methyl ether, polyvinyl acetal, polyacrylic acid and its salts, polyethylene oxide, vinyl acetate-polyvinyl pyrrolidone copolymer, styrene-acrylic acid copolymer and its salts, isobutylene maleic anhydride copolymer and its salts can be used.
[0055] The content of the dispersant can be appropriately selected to satisfy the above-mentioned ratio of the dispersant to the carbon black. The content of the dispersant can be, for example, 0.1% by mass or more, 0.3% by mass or more, 0.5% by mass or more, 0.7% by mass or more, 0.9% by mass or more, 1.0% by mass or more, 1.1% by mass or more, 1.3% by mass or more, or 1.5% by mass or less, or 6.0% by mass or less, or 5.5% by mass or less, or 5.0% by mass or less, or 4.5% by mass or less, or 4.0% by mass or less, or 3.5% by mass or less, or 3.0% by mass or less, or 2.8% by mass or less, or 2.5% by mass or less, relative to the mass of the aqueous dispersion for forming the electromagnetic wave shielding film.
[0056] 〈Urethane dispersion〉
[0057] The urethane dispersion is a dispersion of particles used as a binder for carbon black (dispersion), and a dispersion provided in the form of an aqueous dispersion can be used.
[0058] The average particle size of the particles of the urethane dispersion measured by laser diffraction method can be 800nm or less, 750nm or less, 700nm or less, 650nm or less, 600nm or less, 550nm or less, 500nm or less, 450nm or less, 400nm or less, 350nm or less, 300nm or less, 250nm or less, 230nm or less, 200nm or less, 170nm or less, 150nm or less, 130nm or less, 110nm or less, 100nm or less, 90nm or less, 80nm or less, 70nm or less, 60nm or less, 50nm or less or 40nm or less. The average particle size used in this specification is the value of the median particle size (D50) calculated based on the volume basis in the laser diffraction method. The measurement using the laser diffraction method can be carried out using, for example, a particle size distribution measuring device MT3300II (MicrotracBEL).
[0059] From the perspective of suppressing the shrinkage when the aqueous dispersion for forming the electromagnetic wave shielding film is applied to the resin substrate, the content of the particles of the carbamate dispersion is preferably 3% by mass or more, 4% by mass or more, or 5% by mass or more relative to the mass of the aqueous dispersion for forming the electromagnetic wave shielding film. The content may also be 15% by mass or less, 13% by mass or less, or 11% by mass or less. In addition, at a content within such a range, the surface resistivity of the obtained electromagnetic wave shielding film becomes a low value, thereby achieving good electromagnetic wave absorptivity.
[0060] Volatile alkali
[0061] As the volatile base, a base that can be volatilized by a drying process, particularly a base having a vapor pressure of more than 1 mmHg at 25° C. can be used. As such a volatile base, for example, ammonia, urea, monoethanolamine, diethanolamine, triethanolamine, aminomethylpropanol, etc. can be used. These can be used alone or in combination.
[0062] The content of volatile alkali relative to the mass of the aqueous dispersion used to form the electromagnetic wave shielding film can be more than 0.1 mass%, more than 0.3 mass%, more than 0.5 mass%, more than 0.7 mass%, more than 1.0 mass%, more than 1.1 mass%, more than 1.3 mass%, more than 1.5 mass% or more than 1.7 mass%, and can also be less than 3.0 mass%, less than 2.8 mass%, less than 2.5 mass%, less than 2.2 mass% or less than 2.0 mass%.
[0063] 〈Gelling agent〉
[0064] As the gelling agent, for example, an alkali swelling type, particularly an alkali swelling associative type, is preferably used from the viewpoint of maintaining the dispersed state of carbon black in the aqueous dispersion for forming the electromagnetic wave shielding film and thereby improving the electromagnetic wave absorptivity of the obtained electromagnetic wave shielding film.
[0065] Here, the "alkali-swellable" gelling agent refers to an unneutralized acrylic polymer, which mainly contains acid groups such as carboxyl groups in the three-dimensional structure of the polymer, and is first swelled by alkali neutralization and then further neutralized to finally dissolve.
[0066] In the present invention, among the alkali-swellable gelling agents, alkali-swellable associative gelling agents are preferably used. Here, the "alkali-swellable associative" gelling agent refers to a gelling agent that exhibits thickening properties by associating the hydrophobic part of the molecule with the hydrophobic part of other molecules when the polymer swells, thereby forming loose bonds between the molecules.
[0067] It can be considered that the alkali swelling associative type gelling agent has two kinds of thickening effects. The first thickening effect refers to the effect of improving viscosity by dissolving only in the alkaline region in the mixed part with water or polar solvent, and the hydrophilic groups such as carboxyl groups in the molecule undergo hydration and swelling, becoming steric hindrance in the solution. The second thickening effect refers to the effect of improving viscosity by associating and adsorbing the hydrophobic groups and hydrophilic groups in the molecule with the components in the ink, such as the pigment, solvent, and surfactant, respectively, to form a network-like aggregate.
[0068] As the alkali-swellable associative gelling agent of the present invention, a polymer having a carboxyl group and a hydrophobic group can be used. Examples of the hydrophobic group include a chain or cyclic hydrocarbon group, an aromatic hydrocarbon group, a halogenated alkyl group, an organic silicon group (-SiR3), a fluorinated carbon group (-C n F 2n+1 ) etc. Specific examples of the polymer include polyacrylic acid, polymethacrylic acid, polyacrylic acid copolymers, and polymethacrylic acid copolymers.
[0069] From the perspective of obtaining an electromagnetic wave shielding film of the desired thickness, the content of the gelling agent relative to the mass of the aqueous dispersion for forming the electromagnetic wave shielding film is preferably 0.03 mass %, 0.05 mass %, 0.07 mass %, 0.10 mass % or 0.12 mass % or more. In addition, from the perspective of the coating suitability of the aqueous dispersion for forming the electromagnetic wave shielding film, it is preferably less than 0.25 mass %, less than 0.22 mass %, less than 0.20 mass %, less than 0.18 mass % or less than 0.15 mass %.
[0070] 《Method for manufacturing electromagnetic wave absorbing sheet》
[0071] The method of the present invention for producing an electromagnetic wave absorbing sheet comprises the steps of applying the above-mentioned aqueous dispersion on a resin substrate and drying the dispersion to obtain an electromagnetic wave shielding film.
[0072] The surface resistivity of the electromagnetic wave shielding film thus obtained measured by the four-probe method can be 400Ω / □ or less, 380Ω / □ or less, 350Ω / □ or less, or 320Ω / □ or less. The surface resistivity can be, for example, 100Ω / □ or more, 150Ω / □ or more, or 180Ω / □ or more. With such a surface resistivity, good electromagnetic wave absorptivity of the electromagnetic wave shielding film can be obtained. The probe spacing of the four-probe method is 10 mm.
[0073] The coating can be performed using an applicator, a bar coater, an inkjet printer, a comma coater, a gravure coater, a screen or the like.
[0074] As the resin substrate, for example, polyolefin resins such as polypropylene, polyester resins such as polyethylene terephthalate, polyamide resins such as nylon and aramid, polycarbonate, etc. can be used.
[0075] Electromagnetic wave absorbing sheet
[0076] The electromagnetic wave absorbing sheet of the present invention comprises a resin substrate and an electromagnetic wave shielding film on the resin substrate. The electromagnetic wave shielding film is a film obtained by drying the aqueous dispersion according to claim 1 or 2, and is particularly a film obtained by the above method.
[0077] The DRY film thickness of the electromagnetic wave shielding film may be 100 μm or less. The DRY film thickness may be 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, 15 μm or less, 12 μm or less, 10 μm or less, 7 μm or less, or 5 μm or less. The DRY film thickness may be measured using a stylus-type surface shape measuring instrument such as Dektak of BRUKER.
[0078] The volume resistivity of the electromagnetic shielding film may be 1.0 Ω·cm or less, 0.8 Ω·cm or less, 0.5 Ω·cm or less, 0.4 Ω·cm or less, or 0.3 Ω·cm or less. The volume resistivity is measured at an ambient temperature of 25° C. and a relative humidity of 40% RH according to JIS C 2139:2008.
[0079] Example
[0080] The present invention is specifically described by way of Examples and Comparative Examples, but the present invention is not limited thereto.
[0081] 《Preparation of aqueous dispersion for forming electromagnetic wave shielding film》
[0082] <Example 1>
[0083] An aqueous dispersion for forming an electromagnetic shielding film of Example 1 was prepared by mixing 60 parts by mass of a carbon black toner, 15 parts by mass of a urethane dispersion, 1 part by mass of a surfactant, 1 part by mass of triethylamine (TEA), and 0.1 parts by mass of an antiseptic.
[0084] The carbon black toner contained 7.8 parts by mass of carbon black (CB), 0.78 parts by mass of aminomethyl propanol (AMP), 1.56 parts by mass of styrene acrylic resin (SA) as a dispersant, and 49.86 parts by mass of water.
[0085] The urethane dispersion used here is an aqueous urethane dispersion in which particles of the urethane dispersion are dispersed in water.
[0086] <Examples 2 to 7 and Comparative Examples 1 to 24>
[0087] Except having changed the substances used and the contents as shown in Tables 1 to 4, the same procedure as in Example 1 was carried out to prepare aqueous dispersions for forming electromagnetic shielding films of Examples 2 to 7 and Comparative Examples 1 to 24.
[0088] The details of other substances shown in Tables 1 to 4 are as follows. In addition, for substances whose solid content is described, the mass of the solid content is described in these tables.
[0089] Carbamate A: HYDRAN WLS201 (DIC Co., Ltd., solid content 35%, average particle size 35nm)
[0090] Carbamate B: HYDRAN WLS213 (DIC Co., Ltd., solid content 35%, average particle size 27nm)
[0091] Carbamate C: HYDRAN HW-920 (DIC Co., Ltd., solid content 50%, average particle size 204nm)
[0092] Styrene Acrylic A: JONCRYL 52J (BASF Japan Co., Ltd., Tg56°C, dissolved, solid content 60%)
[0093] Styrene acrylic B: JONCRYL JDX6180 (BASF Japan Co., Ltd., Tg134°C, dissolved, solid content 27%)
[0094] Acrylic acid A: JONCRYL PDX-7780 (BASF Japan Co., Ltd., Tg 92°C, average particle size 114 nm, solid content 48%)
[0095] Acrylic acid B: JONCRYL PDX-7734 (BASF Japan Co., Ltd., Tg 40°C, average particle size 73 nm, solid content 41.4%)
[0096] Acrylic acid C: JONCRYL PDX-7356 (BASF Japan Co., Ltd., Tg 25°C, average particle size 70 nm, solid content 45.5%)
[0097] Acrylic acid D: JONCRYL PDX-7357 (BASF Japan Co., Ltd., Tg-4°C, average particle size 99 nm, solid content 49.5%)
[0098] Acrylic acid E: JONCRYL PDX-7430 (BASF Japan Co., Ltd., Tg 30°C, average particle size 752 nm, self-crosslinking, solid content 38%)
[0099] Acrylic acid F: JONCRYL 352D (BASF Japan Co., Ltd., Tg 56°C, average particle size 99 nm, solid content 45%)
[0100] Acrylic acid G: JONCRYL 89J (BASF Japan Co., Ltd., Tg 98°C, average particle size 114 nm, solid content 48%)
[0101] Acrylic acid H: Ultrasol CMX-235 (AICA Industries, Ltd., Tg-15°C, average particle size 185 nm, solid content 45%)
[0102] Acrylic acid I: Ultrasol LTC-100 (AICA Industries, Ltd., average particle size 216 nm)
[0103] Acrylic acid J: POLYSOL AP-3720N (Tg 9°C, average particle size 147nm, solid content 51%)
[0104] Surfactant: OLFINE 4200, Nissin Chemical Industry Co., Ltd.
[0105] Preservative: BIOSAIDO 1700, Taisho Technos Co., Ltd.
[0106] Dispersant SA: JONCRYL 63J (BASF Japan Co., Ltd., Tg 73°C, dissolving type, solid content 30%)
[0107] "evaluate"
[0108] The prepared electromagnetic wave shielding film-forming aqueous dispersion was applied to the entire surface of a 10 cm×10 cm polyethylene terephthalate film using an applicator with a WET film thickness set to 50 μm. The applied electromagnetic wave shielding film-forming aqueous dispersion was then dried to obtain an electromagnetic wave absorbing sheet having an electromagnetic wave shielding film.
[0109] 〈Coating film shrinkage〉
[0110] The shrinkage of the coating film of the produced electromagnetic wave shielding film was evaluated by visual inspection of the appearance.
[0111] A: A uniform and flat coating film was formed.
[0112] B: Although some surface irregularities were observed, a uniform coating film was formed.
[0113] C: Shrinkage occurred to such an extent that the surface of the polyethylene terephthalate film could be visually confirmed
[0114] D: Shrinkage occurred to such an extent that more than half of the surface of the polyethylene terephthalate film was exposed.
[0115] 〈Adhesion〉
[0116] The adhesion of the electromagnetic wave shielding film is evaluated by a cross-cut test method. Specifically, a plurality of cut grooves are cut in a grid shape at intervals of about 1 mm on the obtained electromagnetic wave shielding film using a cutter. Then, a transparent tape (registered trademark) is pasted to cover the cut grooves, and it is peeled off at an angle of about 60°, and the adhesion state of the electromagnetic wave shielding film on the tape is visually confirmed. The evaluation criteria are as follows.
[0117] A: The electromagnetic wave shielding film is not attached to the tape.
[0118] B: A small amount of the electromagnetic wave shielding film adheres to the tape, but no peeling to such an extent as to affect the appearance of the electromagnetic wave shielding film is observed.
[0119] C: The electromagnetic wave shielding film adheres to the tape, and thus, fragments of the electromagnetic wave shielding film are scattered.
[0120] D: Peeling occurred in many areas of the electromagnetic wave shielding film, but the amount of peeling did not exceed half.
[0121] E: More than half of the electromagnetic wave shielding films peeled off.
[0122] 〈Surface resistivity〉
[0123] For the electromagnetic wave shielding film using adhesives such as "urethane A", "urethane B", "urethane C", "styrene acrylic A", "styrene acrylic B" and "acrylic D" which achieved sufficient results in terms of adhesion, the surface resistivity was measured using a device consisting of a four-probe detector with a probe interval of 10 mm and a resistivity meter mΩHiTESTER3227 (Hioki Electric).
[0124] The configurations and evaluation results of the examples and comparative examples are shown in Tables 1 to 4. Figure 1 middle.
[0125] [Table 1]
[0126]
[0127] [Table 2]
[0128]
[0129] [Table 3]
[0130]
[0131] [Table 4]
[0132]
[0133] The electromagnetic wave shielding film obtained from the aqueous dispersion using a binder other than "urethane A", "urethane B", "urethane C", "styrene acrylic A", "styrene acrylic B" and "acrylic D" failed to obtain sufficient results at least in terms of adhesion.
[0134] In addition, for the cases of using "Urethane A", "Urethane B" and "Urethane C", the measurement results were plotted with the ratio of the mass of the binder to the mass of the carbon black as the horizontal axis and the surface resistivity as the vertical axis, and the quadratic approximation curve obtained from the plotted points is shown in FIG. Figure 1 In the case of using "styrene acrylic acid A" and "acrylic acid D", a quadratic approximation curve is similarly prepared and shown in FIG. Figure 2 middle.
[0135] according to Figure 1 It can be seen that when using "Carbamate A", "Carbamate B" and "Carbamate C", the ratio of the mass of the particles of the carbamate dispersion to the mass of the carbon black is in a smaller range, specifically in the range of 0.55 to 1.30, providing good adhesion and at the same time obtaining a low surface resistivity value, especially in the range of 0.85 to 1.15, the minimum value of the surface resistivity can be obtained.
[0136] 《Evaluation of using gelling agent》
[0137] <Example 1'>
[0138] Using an applicator, the WET film thickness setting value is set to 80 μm, and the electromagnetic wave shielding film forming aqueous dispersion of the above-mentioned Example 1 is applied to the entire surface of a 10 cm×10 cm polyethylene terephthalate film. Next, the applied electromagnetic wave shielding film forming aqueous dispersion is dried to obtain an electromagnetic wave absorbing sheet having an electromagnetic wave shielding film. Based on the electromagnetic wave shielding film obtained in Example 1, the electromagnetic wave shielding film obtained after changing the WET film thickness setting value to 80 μm is recorded as Example 1' in Table 5. Next, the actual measured value of the DRY film thickness of the obtained electromagnetic wave shielding film is measured.
[0139] The DRY film thickness was measured using a stylus-type profilometer (Dektak, BRUKER). The theoretical value of the DRY film thickness was calculated by multiplying the set value of the WET film thickness by the solid content, that is, the total content of CB, binder, and dispersant.
[0140] <Example 8>
[0141] The electromagnetic wave shielding film-forming aqueous dispersion and the electromagnetic wave shielding film of Example 8 were prepared in the same manner as in Example 1, except that the types and contents of the components were changed as shown in Table 5. As a gelling agent, an alkali swelling associative gelling agent (PRIMAL TT-935, Rohm and Haas Japan, solid content 5%) was used. The details of the other substances are the same as in Tables 1 to 4. Next, the measured value and theoretical value of the DRY film thickness of the electromagnetic wave shielding film were obtained in the same manner as in Example 1'.
[0142] <Examples 1'A, 1'B, 1'C, 8A, 8B and 8C>
[0143] The electromagnetic shielding films obtained by further extending the coating distance of the electromagnetic shielding film-forming aqueous dispersion of Examples 1' and 8 were respectively designated as Examples 1'A and 8A. Specifically, a comma coater was used to coat 20 m of the electromagnetic shielding film-forming aqueous dispersion with a WET film thickness setting of 80 μm.
[0144] In addition, electromagnetic wave shielding films obtained in the same manner as Examples 1′, 8, 1′A, and 8A except that the set value of the WET film thickness was changed to 160 μm were respectively designated as Examples 1′B, 8B, 1′C, and 8C.
[0145] Next, in the same manner as in Examples 1′ and 8, the measured value and theoretical value of the DRY film thickness of the electromagnetic wave shielding film were obtained.
[0146] "evaluate"
[0147] Based on the evaluations of the above-mentioned shrinkage, adhesion, and surface resistivity, the volume resistivity of the electromagnetic wave shielding film obtained was calculated according to the following formula.
[0148] Volume resistivity (Ω·cm) = surface resistivity (Ω / □) × DRY film thickness (μm) × 10 -4
[0149] Table 5 shows the configurations and evaluation results of Examples 1 and 5.
[0150] [Table 5]
[0151]
[0152] According to Table 5, at a short coating distance, Example 8 containing a gelling agent has the same performance as Example 1' not containing a gelling agent.
[0153] On the other hand, it can be seen that under the setting values of long coating distance and thick WET thickness, Examples 8A, 8B and 8C have the same performance as Example 1' which does not contain a gelling agent, and compared with Examples 1'A, 1'B, and 1'C, respectively, an electromagnetic wave shielding film with a DRY film thickness close to the theoretical value is obtained.
Claims
1. An aqueous dispersion for forming an electromagnetic wave shielding film, comprising water, carbon black, and a urethane dispersion, The ratio of the mass of the particles of the urethane dispersion to the mass of the carbon black is 0.55 to 1.
30.
2. The aqueous dispersion according to claim 1, wherein The ratio of the mass of the particles of the urethane dispersion to the mass of the carbon black is 0.85 to 1.
15.
3. The aqueous dispersion according to claim 1 or 2, wherein The particles of the urethane dispersion have an average particle size of 50 nm or less as measured by laser diffraction. 4 . The aqueous dispersion according to claim 1 , further comprising a volatile base, wherein the content of the volatile base is 0.1 to 3.0% by mass. The aqueous dispersion according to claim 1 or 2, further comprising a gelling agent.
6. The aqueous dispersion according to claim 5, wherein The gelling agent is an alkali swelling associative gelling agent.
7. The aqueous dispersion according to claim 1 or 2, wherein The carbon black has a hollow shell structure and a BET specific surface area of 1000 m 2 / g or less.
8. A method for producing an electromagnetic wave absorbing sheet, comprising the steps of: coating the aqueous dispersion according to claim 1 or 2 on a resin substrate and drying the dispersion to obtain an electromagnetic wave shielding film.
9. The method according to claim 8, wherein: The surface resistivity of the electromagnetic wave shielding film measured by a four-probe method is 400Ω / □ or less.
10. An electromagnetic wave absorbing sheet comprising a resin substrate and an electromagnetic wave shielding film on the resin substrate, The electromagnetic wave shielding film is obtained by drying the aqueous dispersion according to claim 1 or 2.
11. The electromagnetic wave absorbing sheet according to claim 10, wherein: The electromagnetic wave shielding film has a DRY film thickness of 100 μm or less and a volume resistivity of 1.0 Ω·cm or less.
Citation Information
Patent Citations
Composition for forming electromagnetic wave shielding film, electromagnetic wave shielding film, method for producing electromagnetic wave shielding film, and electronic apparatus
JP2013168399A
Electromagnetic wave-absorbing coating agent, sheet coated with the same, and method for producing the same
JP2015172152A
Electromagnetic wave shielding coating and electromagnetic wave shielding article
JP2015220233A
Electromagnetic wave suppression sheet and electromagnetic wave suppression adhesive sheet including the same
JP2017045782A
Radio wave absorption coating composition, radio wave absorption film, base material with radio wave absorption film and method for producing base material with radio wave absorption film
JP2020111730A
